Assessment of the relationship between metabolic syndrome and breast cancer - Guimarães, Amanda Leal; Antonini, Marcelo; Ferraro, Odair; Real, Juliana Monte; Mattar, André; Lopes, Reginaldo Guedes Coelho (Mastology, 2024)
Introduction: Metabolic syndrome (MS) affects approximately 30% of women aged over 50 years. It is known to have a direct relationship with carcinogenesis and, therefore, with breast neoplasia. Methods: Retrospective longitudinal observational cohort study carried out at the Gynecology and Obstetrics Service of the São Paulo State Public Servant Hospital. The rates of local recurrence, distant metastases and overall survival of patients with malignant breast neoplasia in each group were evaluated. Results: Between 2017 and 2020, 375 patients underwent surgical treatment for breast cancer, of which 335 were eligible for the study, with an average age of 63.4 years old. MS is present in 32.5% of patients. Regarding the prognostic factor, patients with MS have a very similar distribution. The molecular profile in patients with MS is 39.4% of Luminal A patients, while in those without MS it is 42.5% of Luminal B. Regarding clinical staging, patients with MS have initial clinical stage I and IIA in 54 .1% of cases, while patients without MS present an initial clinical stage in 65% of cases. The average overall survival of the sample was 37.3 years, with a CI of 1.1 years; disease-free survival was 35.9 years, with CI 1.2 years; and invasive disease-free survival was 36.9 years, with CI 1.3 years. Conclusions: The presence of MS at diagnosis does not worsen survival.